PENGARUH MODEL PEMBELAJARAN KOOPERATIF TIPE TEAMS-GAME-TOURNAMENT DAN TALKING STICK TERHADAP HASIL BELAJAR MATEMATIKADITINJAU DARI MINAT BELAJAR SISWAKELAS IV SDIT AL-KAUTSARCIKARANG PUSAT - Dadan Hidayat; Gusti Yarmi; Ika Lestari (PARAMETER: Jurnal Pendidikan Universitas Negeri Jakarta, 2021)
This study aims to determine the interaction effect of using the Teams-Games-Tournament and Talking Stick type cooperative learning model with students' interest in learning mathematics. This study uses an experimental post-test control group design. The sample in this study amounted to 66 students who were selected using Cluster Random Sampling. Data collection techniques and instruments: 1) observation, 2) documentation, 3) written test, 4) questionnaire. The results showed that 1) student learning outcomes in the experimental class were higher than the control class, 2) student learning outcomes there were differences between students with high learning interest and low learning interest, 3) student learning outcomes using the Teams-Games-Tournament method. Those who have high learning interest have higher learning outcomes than students who use the talking stick method who have high learning interest. 4) student learning outcomes using the Teams-Games-Tournament method with low learning interest, lower than students using the talking stick method, 5) interaction using the Teams-Games-Tournament and Talking Stick type cooperative learning model with students' learning interest towards mathematics learning outcomes. Abstrak Penelitian ini bertujuan untuk mengetahui pengaruh interaksi penggunaan model pembelajaran kooperatif tipe Teams-Games-Tournament dan Talking Stick dengan minat belajar siswa terhadap hasil belajar matematika. Penelitian ini menggunakan rancangan ekperimental Post-test Control Group Design. Sample dalam penelitian berjumlah 66 siswa yang dipilih menggunakan Cluster Random Sampling. Teknik dan instrumen pengumpulan data: 1) observasi, 2) dokumentasi, 3) tes tulis, 4) kuesioner. Hasil penelitian menunjukkan bahwa 1) hasil belajar siswa pada kelas eksperimen lebih tinggi daripada kelas kontrol, 2) hasil belajar siswa terdapat perbedaan antara siswa yang memiliki minat belajar tinggi dengan minat belajar rendah, 3) hasil belajar siswa yang menggunakan metode Teams-Games-Tournament yang memiliki minat belajar tinggi, lebih tinggi dari hasil belajar daripada siswa yang menggunakan metode talking stick yang minat belajarnya tinggi. 4) hasil belajar siswa menggunakan metode Teams-Games-Tournament yang memiliki minat belajar rendah, lebih rendah daripada siswa yang menggunakan metode talking stick, 5) terdapat interaksi penggunaan model pembelajaran kooperatif tipe Teams-Games-Tournament dan Talking Stick dengan minat belajar siswa terhadap hasil belajar matematika.